NUMERICAL SOLUTION OF SEIRS MODEL OF ONLINE GAME ADDICTION ON MATHMATICS STUDENTS USING HOMOTOPY PERTURBATION METHOD - Nur Rezky Ramadhan; Burhan Burhan (Jurnal Madako Education, 2022)
This study aims to determine the numerical solution of the Homotopy Perturbation method as a solution to a numerical model of SEIRS addiction to online games where the data in this study is secondary data from a closed questionnaire in the form of answer choices given to students. This study has a Suspected-Exposed-Infected-Recovered-Suspected (SEIRS) model. Before determining a numerical solution using the RK-4 method, research was first conducted on the SEIRS model of online game addiction, then performed a simulation, then predicted the number of students' addiction to online games. The simulation results using the MAPLE application and this research can be used as a benchmark for parents and students regarding restrictions on the use of online games.Keywords: Homotopy Perturbation Method, Online Game, SEIRS.